Cardioprotective effects and nutrigenomic study of edible bird's nest In vitro and In vivo - Zhang, Yida (2016)
Cardiovascular disease (CVD) is one of the major cause of morbidity and mortality globally, which is contributed by multiple risk factors including hyperlipidemia, insulin resistance, hypercoagulation, inflammation and oxidative stress. Current therapies have several limitations and are not able to tackle all metabolic perturbations related to CVD. Alternative therapies like edible birds nest (EBN) are therefore receiving closer attention. EBN has been used for thousands of years to improve wellbeing in Asia but there is lack of scientific evidence to back up its use. The present work focused on the cardioprotective effects of edible bird’s nest and the nutrigenomic basis for such effect, in vitro and in vivo. In vitro antioxidant potentials of EBN extracts were determined by 2,2′-azinobis- (3-ethylbenzothiazoline-6- sulfonic acid) (ABTS) and oxygen radical absorbance capacity (ORAC) assays, while their effects against oxidative stress were tested in HepG2 cell line. The results showed that EBN extracts possessed potent antioxidant potentials especially after simulated gastrointestinal digestion; at 1000μg/mL, there was up to 50% radical scavenging without signs of toxicity. This was followed by in vivo testing of the EBN using a high fat diet induced hyperlipidemic Sprague Dawley rat model, in which high fat diet (HFD)+2.5%EBN, HFD+20%EBN, HFD+10mg/kg/day simvastatin, HFD alone and normal pellet were fed to different rat groups for 12 weeks. The results showed that the EBN groups improved HFD-induced hyperlipidemia (total cholesterol = 6.04 mmol/L (19.14%), triglyceride = 0.54 mmol/L (55.37%), and low density lipoprotein = 4.52 mmol/L (9.24%) for HFD+2.5%EBN, and 4.17 mmol/l (44.18%), 0.44 mmol/L (63.64%), 2.98 mmol/L (40.16%) for HFD+20%EBN, respectively), similar to simvastatin (4.99 mmol/L (33.20%), 0.63 mmol/L (47.93%) and 3.6 mmol/L (27.71%), respectively) in comparison with the HFD alone group (7.47 mmol/L, 1.21 mmol/L and 4.98 mmol/L, respectively). EBN also lowered the risk of HFD-induced insulin resistance unlike simvastatin which increased such risk (homeostatic model of insulin resistance was 1.63±0.71, 2.83±0.79 and 2.46±0.22 for HFD+20%EBN, HFD+simvastatin and HFD alone, respectively). EBN also improved HFD-induced inflammation, oxidative stress and coagulation as evidenced by attenuation of HFD-induced alterations of Tumor necrosis factor-alpha (TNF-α), Interleukin-6 (IL-6), C-reactive protein (CRP), ABTS, Thiobarbituric acid reactive substances (TBARS), Activated partial thromboplastin time (APTT), Prothrombin time (PT), Bleeding time (BT), Platelet count (PC),Oxidized low density lipoprotein (OxLDL), platelet aggregation, leptin, adiponectin and Nitric oxide synthase 3 (NOS3). Furthermore, HFD-induced transcriptional changes were attenuated by EBN; HFD+20% EBN group showed upregulation of the insulin receptor substrate 2 (IRS2), phosphatidyl inositol-3-kinase (PI3K), glucokinase (GCK), gluthatione reductase (Gsr), superoxide dismutase (SOD) and gluthatione peroxidase (Gpx) genes, and downregulation of the inhibitor of nuclear factor kappa-B kinase subunit beta (IKBKB), mitogen-activated protein kinase 1 (MAPK1), Chemokine (C-C motif) ligand 2 (Ccl2), C-reactive protein (CRP), nuclear factor kappa beta1 (Nfkb1), tumor necrosis factor (TNF), von willibrand factor (vWF) and plasminogen activator inhibitor-1 (PAI-1) genes which were the possible basis for the improved insulin resistance, inflammation, oxidative stress and coagulation. EBN was also found to be predominantly protein (57%) of EBN, and sialic acid was the major protein constituent (11%) of EBN. Sialic acid was therefore tested to determine if it was a major contributor to the effects of EBN, with results showing that it contributed significantly as evidenced by similar effects it produced in comparison with the EBN treatment. The findings thus far suggests that EBN and sialic acid may be good candidates for cardioprotection through regulation of hyperlipidemia, insulin resistance, inflammation, oxidative stress and hypercoagulation which are all linked with cardiovascular disease.